Forward Contracts and Firm Value: Investment Incentive and Contracting Effects - Bessembinder, Hendrik (Journal of Financial and Quantitative Analysis, 1991)
Corporate risk hedging with forward contracts increases value by reducing incentives to underinvest. This occurs because the hedge decreases the sensitivity of senior claim value to incremental investment, allowing equity holders to capture a larger portion of the incremental benefit from new investment. Hedging also allows the firm to credibly commit to meet obligations in states where it otherwise could not, which improves contract terms the firm can negotiate with customers, creditors, and managers. These benefits cannot be duplicated by individual hedging, and each result holds independent of agents' risk preferences.